2018
DOI: 10.1186/s12938-018-0487-3
|View full text |Cite
|
Sign up to set email alerts
|

Mobile GPU-based implementation of automatic analysis method for long-term ECG

Abstract: BackgroundLong-term electrocardiogram (ECG) is one of the important diagnostic assistant approaches in capturing intermittent cardiac arrhythmias. Combination of miniaturized wearable holters and healthcare platforms enable people to have their cardiac condition monitored at home. The high computational burden created by concurrent processing of numerous holter data poses a serious challenge to the healthcare platform. An alternative solution is to shift the analysis tasks from healthcare platforms to the mobi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 31 publications
1
0
0
Order By: Relevance
“…In addition, GPU reduced the logic control unit and cache in the data processing process, thereby improving computational efficiency [ 19 ]. This was consistent with the findings of Fan et al [ 20 ]. It was also found that the running time of the program using shared memory was about 4.8 times shorter than that of the program not using shared memory.…”
Section: Resultssupporting
confidence: 94%
“…In addition, GPU reduced the logic control unit and cache in the data processing process, thereby improving computational efficiency [ 19 ]. This was consistent with the findings of Fan et al [ 20 ]. It was also found that the running time of the program using shared memory was about 4.8 times shorter than that of the program not using shared memory.…”
Section: Resultssupporting
confidence: 94%